Comparison of wood, fibre and vessel properties of drought-tolerant eucalypts in South Africa§. Issue 3 (3rd July 2017) - Lundqvist, Sven-Olof; Grahn, Thomas; Olsson, Lars; Seifert, Thomas
Abstract : Three drought-tolerant eucalypt genotypes have been investigated for a broad spectrum of properties to provide a basis for comparison on their suitability for various end-uses. The genotypes included were a Eucalyptus grandis × E. camaldulensis hybrid, E. gomphocephala and E. cladocalyx, selected based on previous studies that indicated good potential to tolerate arid conditions, reasonably good volume growth and straightness of stems. In this study, information was added on differences between species and parts of stems in growth (volume and biomass) and properties of wood (density and stiffness), fibres (dimensions and microfibril angle) and vessels (size and numbers). We found high wood densities and stiffness values for E. cladocalyx and E. gomphcephala, making them suitable for construction wood. Logs from the mid-part of the stem had the best timber properties, as the butt logs showed the highest microfibril angle and lowest wood stiffness due to longitudinal juvenility. Such juvenility was also to some degree observed for wood density and fibre length. The information gained will be especially helpful for selecting species and processing options for small farm and community plantations for producing higher-value products that may be sold to generate much-needed income as well as for local uses, such as fuelwood and charcoal.